Intergenerational Social Mobility in Africa Since 1920 - Ouedraogo, Rasmane (IMF Working Papers; Working Paper ;, 2021)
The COVID-19 crisis has a severe impact on education and employment and exposed the many social inequities that make some populations more vulnerable to shocks. Despite a vast literature on social mobility in advanced economies, little is known about it in African countries, mainly due to data limitations. Using a large harmonized dataset of more than 72 million individuals, we fill this gap and examine socioeconomic status mobility across generations, measured by educational and occupational attainment. We uncover the substantial geographical variations in the degree of upward/downward educational and occupational mobility across and within African countries, and the gender and rural/urban divide. Additionally, we explore the determinants of social mobility in the African region. We find that social mobility on the continent could be partly explained by observable individual characteristics (gender, marital status, age, et cetera), and that educational mobility is a driver of occupational mobility. Lastly, we show that the quality of institutions, the level of public spending on education, social protection coverage, natural resource endowments, and countries' fragility are strong predictors of social mobility in Africa.